IDENTIFICATION OF RESIDUAL SOLVENTS BY USING GC – HS METHOD FOR EZETIMIBE (Cuestiones de Fisioterapia, 2025)
A Simple, Specific, sensitive, accurate, robust, precise GC -HS Method was developedand validated for stability indicating analytical method development and validation for identificationof residual solvents for Ezetimibe drug. The method was developed by using DMSO (DimethylSulphoxide) as a mobile phase. The Column used for separation was ZB-624 with dimensions as 30m x0.53mm, 3.0 µm thickness with flow rate 2.0ml/min and Injector temperature is 2000c and 260 0cdetector temperature with the split ratio is 1:5 and with run time 25 min and constant flow 2.0 ml/min.The validation was carried out on the optimised method and the obtained results were within the limitsof acceptance criteria for parameters like System suitability, Specificity, Linearity, Accuracy,Precision, LOD, LOQ, Robustness and the stability of the method has been checked by solutionstability studies. Based on the above information the method can be used for daily routine analysis.